Considerations on ’informed consent’ in practical medicine and clinical trials - Fasoli, Angelo (Medicina e Morale, 2024)
The patient's 'informed consent' represents one of the most debated and even, to a certain extent, controversial topics in medicine today. The issue of consent concerns all aspects of medical intervention, both in individual medical practice and in clinical trials.